Vulnerability and adaptation of rural households livelihoods to climate change in the Eastern Cape, South Africa: perspectives on the asset-based adaptation framework - Amoah, Laura Novienyo Abla (My University, 2019)
The purpose of this study was to investigate how climate change affects the rural poor, and how the rural poor respond and adapt to rural food security. Fieldwork data were obtained from three different rural communities namely, Mgugwana, Manaleni, and Ndayini. These communities are located in Port Saint John’s Local Municipality in the Eastern Cape, South Africa. Primary data were obtained using semi-structured questionnaires, interviews, observations, and focus group discussions. Data obtained from closed-ended questions were analysed using basic statistics and organised in frequency tables and graphs. The open-ended and focused group interviews were transcribed and similar themes were identified and reported. Several responses from the open-ended questions were also reported verbatim. The findings suggest that climate change significantly affect food security in all three rural communities. Prolonged drought occurs during the summer season and this impact negatively on their agricultural production. The findings also reveal that farmers have knowledge of, and have implemented different adaptation and coping strategies during extreme weather conditions. However, farmers were not able to adequately produce food in their farms to ensure food security. Lack of irrigation facilities and persistent drought emerged as contributing factors to food insecurity in the area. Factors such as soil infertility, low crop production, hunger, school dropout, unemployment, death of livestock, high crime rates, damage to roads and bridges, destruction of homes and houses, and poor health were the effects of climate change on rural household livelihood assets. Based on the above findings it is recommended that government should renew its political will to direct policy formulation and implementation to assist rural communities and rural farmers to mitigate the impact of climate change. The policies should focus on education, reformed adaptation, and coping strategies. The government should also establish and capacitate institutions (such as the South African Weather Services, Department of Agriculture, Forestry and v Fisheries) to provide relief and early warning information to rural communities of potential extreme weather conditions. The government should also invest in the building of dams and provision of irrigation facilities to rural farmers especially those living in the three communities involved in the study. The local municipality should establish programs or projects (e.g. supply of seedlings) to encourage and support rural gardening and rural agriculture especially for the rural poor. It is also recommended that the local municipality should liaise with the national government to provide financial assistance to rural farmers to acquire farm implements that can assist them to reduce the effect of climate change. Finally, the government in partnership with private donor institutions should formulate a long-term policy focusing on post-climate crises management for rural poor communities. The proposed framework in this study can serve as an important guide. Finally, both theoretical and practical contributions are achieved. The study has contributed to advancing the scholarly knowledge of rural households’ adaptation strategies to CC using the assets-based framework. Practically, the recommendations and proposed framework will contribute to empowering the society specifically those in rural communities to be resilient in the event of extreme climate change.
A thesis submitted to the Faculty of Science in fulfilment of the requirement for the degree Doctor of Philosophy (PhD) in department of Geography, Archaeology and Environmental Studies, University of the Witwatersrand, Johannesburg, 2019